2018
DOI: 10.2174/1568009617666170427110450
|View full text |Cite
|
Sign up to set email alerts
|

CX-4945, a Selective Inhibitor of Casein Kinase 2, Synergizes with B Cell Receptor Signaling Inhibitors in Inducing Diffuse Large B Cell Lymphoma Cell Death

Abstract: These findings suggest a role for CK2 downstream of the BCR in controlling survival pathways crucial for cell growth of different DLBCL subtypes. Also, the use of CX-4945 in combination with BCR signaling blockers could represent a novel rational therapeutic approach in the DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Hazan-Haley et al [35] first demonstrated that in CLL STAT3 is constitutively phosphorylated on Ser727, regardless of clinical parameters, being translocated into the nucleus by the karyopherin-beta nucleocytoplasmic system and bound to p21 and c-Myc genes. Serine phosphorylation of STAT3 is regulated by an aberrant cytoplasmic complex of CD5, BLNK, and CK2 (a pleiotropic serine/threonine kinase [36]) [37]. Moreover, it has been published that both IL-6, through the recruitment of JAK2, and the BCR, through a JAK2-independent mechanism, can promote STAT3 phosphorylation on Tyr705 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Hazan-Haley et al [35] first demonstrated that in CLL STAT3 is constitutively phosphorylated on Ser727, regardless of clinical parameters, being translocated into the nucleus by the karyopherin-beta nucleocytoplasmic system and bound to p21 and c-Myc genes. Serine phosphorylation of STAT3 is regulated by an aberrant cytoplasmic complex of CD5, BLNK, and CK2 (a pleiotropic serine/threonine kinase [36]) [37]. Moreover, it has been published that both IL-6, through the recruitment of JAK2, and the BCR, through a JAK2-independent mechanism, can promote STAT3 phosphorylation on Tyr705 [38].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, fostamatinib (which inhibits PLK1 as well as other serine-threonine kinases) was shown to be effective against the prostate cancer cell line (PC3) [102]. The anti-cancer activity of fostamatinib was also evident against head and neck squamous cell carcinoma [103], hepatocellular carcinoma [104], breast cancer [105], and diffuse large B cell lymphoma [106] cell lines. Moreover, a fostamatinib derivative, NSC765691, also exhibited antiproliferative activity against the panel of NCI-60 cell lines [107].…”
Section: Discussionmentioning
confidence: 98%
“…CK2 was found overexpressed also in a panel of GC‐ and ABC‐type DLBCL cell lines and its inactivation with Silmitasertib caused apoptosis accompanied by a downmodulation of the CK2 phospho‐substrates CDC37 and NF‐κB p65/RelA . The following work has further investigated more in depth the consequences of CK2 inhibition with Silmitasertib on a panel of DLBCL cell lines, especially looking at signaling cascades emanating from the BCR and the synergy/cooperation with BCR signaling inhibitors . CK2 inhibition caused apoptosis of both GC‐ and ABC‐type DLBCL cells and a marked downregulation of the PI3K/AKT signaling cascade.…”
Section: Ck1 and Ck2 In Lymphoid Malignanciesmentioning
confidence: 94%
“…Moreover, the BCR signals were markedly impaired as judged by the dramatic down‐modulation of the spike of cytosolic Ca ++ concentration upon stimulation of the BCR. Intriguingly, equal cytotoxic activity was observed also in “double hit” lymphoma cells …”
Section: Ck1 and Ck2 In Lymphoid Malignanciesmentioning
confidence: 99%